An audit of COPD: diagnosis and management in general practice. Issue 4 (23rd November 2020) - Hamad, Ghassan; Rigby, Alan; Morice, Alyn H.
Introduction: COPD is a spectrum of disorders primarily caused by smoking and characterised by progressive, not fully reversible airflow obstruction with a forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC) ratio <0.7. Methods: From November 2016 to March 2017 we audited patients with COPD in five general practices in Hull and East Riding, UK. We looked at deviation from the locally agreed guidelines. We extracted data on severity, exacerbations, medication and eosinophil count. Results: We assessed 1088 records. Median age was 70.9 years; 577 (53%) were male. About two-thirds of patients on the COPD register have an FEV1 /FVC ratio in the diagnostic range for COPD, however, 388 (36%) out of 1088 had a ratio of ≥0.7. In the patients with a ratio of ≥0.7, 259 (67%) out of 388 had an FEV1 <80% of predicted. Patients with frequent exacerbations were more likely to be prescribed inhaled corticosteroid (ICS)-containing inhalers (incidence rate ratio of 2). FEV1 % predicted was a poor indicator of exacerbation frequency; however, the presence of elevated blood eosinophil counts (EOS) on at least two occasions was highly predictive of exacerbations. When ICSs, FEV1, EOS were examined in combination, they were highly significant predictors for exacerbations. Conclusion: FEV1 maybe a more accurate diagnostic parameter in primary care. Historical evidence of blood eosinophilia is a better predictor than FEV1 . The combination of biomarkers may prove more accurate indicator of future exacerbation frequency, leading to targeted intervention. FEV1 <80% predicted provides a greater concordance with the primary care clinical diagnosis of COPD. When blood eosinophilia is coupled with ICS prescription and FEV1, a much-enhanced predictability of exacerbation is achieved. https://bit.ly/2PtYS83